Pro Bono Work and Trust in Expert Fields - David Ong; Chun-Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2014)
A controversy has been simmering in law for at least 30 years about whether pro bono work should be mandatory for lawyers, who now donate 1-3% of their time to the poor. This has centered on the unmet legal needs of the poor, the duty of lawyers, and the contrast with US doctors, who are conspicuous in their tradition of voluntary pro bono work. In 2003 alone, they donated 12 billion of labor amounting to 5-10% of their time. This debate has tended to neglect the credence good aspect of the services of experts (e.g., of doctors, lawyers, and accountants), and the role that voluntary pro bono work might play. Expert services have un- verifiable quality to non-experts and are subject to moral hazard. Experts who cheat their customers should crowd out experts who do not, resulting in low trust, prestige, and wages. We ask how pro bono work might promote trust in expert fields. We introduce incomplete information into a psychological game theoretic model of experts who value the esteem from their customers. In our model, pro bono work arises in equilibrium because experts who value the perception of honesty among their customers more are also more willing to give away labor to the poor to signal their honesty. We show that if the aversion to disappointing this esteem is sufficiently high, there is a unique equilibrium in which their wages are high, they do pro bono work, and experts who would have been dishonest are crowded out of the field. Our novel approach involving psychological factors suggests that while mandatory pro bono could redistribute surplus from experts to the poor, it could also undermine the screening effect of pro bono work, and thus, cause a deterioration in service quality.
Keywords: C72; L30; M50; 330; psychological games; guilt; honor; experts; credence goods